An overview of solar photovoltaic panels' end-of-life material recycling. (January 2020) - Chowdhury, Md. Shahariar; Rahman, Kazi Sajedur; Chowdhury, Tanjia; Nuthammachot, Narissara; Techato, Kuaanan; Akhtaruzzaman, Md.; Tiong, Sieh Kiong; Sopian, Kamaruzzaman; Amin, Nowshad
Abstract: End-of-life (EOL) solar panels may become a source of hazardous waste although there are enormous benefits globally from the growth in solar power generation. Global installed PV capacity reached around 400 GW at the end of 2017 and is expected to rise further to 4500 GW by 2050. Considering an average panel lifetime of 25 years, the worldwide solar PV waste is anticipated to reach between 4%-14% of total generation capacity by 2030 and rise to over 80% (around 78 million tonnes) by 2050. Therefore, the disposal of PV panels will become a pertinent environmental issue in the next decades. Eventually, there will be great scopes to carefully investigate on the disposal and recycling of PV panels EOL. The EU has pioneered PV electronic waste regulations including PV-specific collection, recovery and recycling targets. The EU Waste of Electrical and Electronic Equipment (WEEE) Directive entails all producers supplying PV panels to the EU market to finance the costs of collecting and recycling EOL PV panels in Europe. Lessons can be learned from the involvement of the EU in forming its regulatory framework to assist other countries develop locally apposite approaches. This review focused on the current status of solar panel waste recycling, recycling technology, environmental protection, waste management, recycling policies and the economic aspects of recycling. It also provided recommendations for future improvements in technology and policy making. At present, PV recycling management in many countries envisages to extend the duties of the manufacturers of PV materials to encompass their eventual disposal or reuse. However, further improvements in the economic viability, practicality, high recovery rate and environmental performance of the PV industry with respect to recycling its products are indispensable. Highlights: Global installed PV reached around 400 GW at the end of 2017 and is expected to rise further to 4500 GW by 2050. The worldwide solar PV waste is estimated to reach around 78 million tonnes by 2050. The current status of the EOL PV panels are systemically reviewed and discussed. Policy formation involving manufacturer's liability to inspire recycling of waste solar panels. R&D needs acceleration allowing researchers to resolve issues in PV module recycling.